El postestructuralismo como punto de intersección entre medio ambiente y sociedad. (2010)
The rise of Postmodernism entailed a fundamental paradigm shift that managed to dissolve the existing duality between Environment and Society. The article aims to illustrate briefly the main theoretical trends that have eroded the abovementioned duality by introducing the concept of Environment in the study of social phenomena. Semiotic Marxism will be addressed as the starting point and theoretical platform to all arenas of social theory production which stress the research issue; such as Political Ecology; Ecologic Marxism and Ecologic Feminism among others. Finally; the Foucauldian concept of Knowledge/Power will be ascertained in order to demonstrate how the so called Eco-Knowledge or Green Knowledge has managed to redefine State Sovereignity by creating international environmental disciplinary standards replacing domestic laws via multilateral organizations such as the World Bank or the International Monetary Fund.